Papillary thyroid carcinoma metastasis most probably due to fine needle aspiration biopsy - Tamiolakis, Dimitrios (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Implantation of cancer cells from needle biopsy has been reported in a wide range of malignancies. Fine needle aspiration biopsy has become an accepted method for assessment of thyroid nodules. Local reappearance of thyroid cancerfrom needle track dissemination is a rare complication of thyroid aspiration. A 45-year-old female developed local recurrence of papillary thyroid carcinoma four years after aspiration biopsy and thyroidectomy. Metastatic deposits appeared in the skin and the sternocleidomastoid muscle. The linear array and the site of metastases implied that seeding most probablyresulted from the needle biopsy.
Keywords: Adverse Effects; Biopsija igelna; Biopsy, Needle; Carcinoma, Papillary; Karcinom papilarni; Kožne novotvorbe; Middle Age; Neoplasm Seeding; Novotvorba, razsev; Secondary; Skin Neoplasms; Srednja leta; Ščitnica, novotvorbe; Thyroid Neoplasms